A negative electrode sheet, a method for manufacturing the same, and a secondary battery
Patent Information
- Application Number
- CN202611336399.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
工艺优化方面,多级低温烘干(如80℃→100℃→120℃)可降低溶剂挥发速率,但会使烘干效率下降40%
(1)本发明通过增加底涂层,利用底涂粘结剂和SBR的交联反应,改善了粘结剂的上浮问题。
Smart Images

Figure CN123017857A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and more specifically, relates to a negative electrode sheet, its preparation method, and a secondary battery. Background Technology
[0002] The new energy industry (such as power batteries and energy storage batteries) is currently experiencing explosive growth, with global lithium battery production capacity exceeding 3TWh in 2024. The industry's requirements for production efficiency (such as coating speed), cell energy density, and cycle life are continuously increasing. However, in the core process of aqueous negative electrode coating, the problem of binder (mainly styrene-butadiene rubber SBR) floating not only causes the slurry to turn blue and uneven electrode bonding, but also triggers a chain reaction of subsequent problems such as weak peel force and powder shedding during cycles, seriously affecting mass production consistency and cell reliability, necessitating targeted technological breakthroughs.
[0003] In SBR anode systems, binder flotation is a frequent pain point in mass production. During the slurry stage, after standing for ≥4 hours, free SBR will float to the surface, forming a blue floating layer, requiring frequent stirring and adjustment. During the coating and drying stage, after the wet electrode enters the oven, the solvent (deionized water) evaporates at a rate of 0.5-2.0 g / (m²). SBR migrates to the surface of the electrode with solvent vapor, and the binder content on the surface of the electrode is 2-5 times higher than that on the bottom layer. This uneven distribution directly leads to a generally low peel force of the negative electrode. The binder also has problems such as rolling and sticking to the rollers when it floats to the surface. There are also risks such as active material powder falling off after the cell is cycled and water drop during the cycle.
[0004] The essence of binder flotation is driven by both physical migration and interfacial interactions. During the drying of wet electrode sheets, the solvent evaporates from the inner layer to the outer layer, forming a "concentration gradient." As a light component with a density of approximately 1.02 g / cm³, SBR moves towards the surface with the solvent vapor under the action of capillary forces of 10-50 Pa. The migration rate increases, especially when the oven temperature gradient exceeds 15 °C / m. At the same time, in order to improve production capacity, the current coating speed has been increased from the traditional 30 m / min to over 60 m / min. The residence time of the wet electrode sheet in the oven is greatly shortened, and the solvent evaporation is more intense, further aggravating SBR flotation.
[0005] While the industry currently mitigates surface drift through process optimization and formulation adjustments, these methods all have significant limitations. Regarding process optimization, multi-stage low-temperature drying (e.g., 80℃→100℃→120℃) can reduce solvent evaporation rates, but it also decreases drying efficiency by 40%. As for formulation adjustments, adding high-viscosity thickeners (such as guar gum) can slow SBR migration by increasing slurry viscosity, but it easily leads to poor slurry flowability and coating surface density fluctuations of ±5%, failing to completely solve the problem. These methods are mostly "passive suppression," failing to address the fundamental issue of interfacial bonding, and generally suffer from an "efficiency-performance" contradiction, making them unsuitable for the industry's triple demands of high capacity, low cost, and long lifespan. Summary of the Invention
[0006] The purpose of this invention is to provide a negative electrode sheet, its preparation method, and a secondary battery. This invention improves the problem of binder floating by adding an undercoat layer and utilizing the crosslinking reaction of the undercoat binder and SBR.
[0007] To achieve the above objectives, a first aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising: (1) A primer slurry is coated on the upper and lower surfaces of the copper foil to form a primer coating; wherein the slurry includes a primer adhesive, and the primer adhesive is a polyacrylic polymer containing at least one crosslinking functional group selected from nitrile, phenyl, epoxy, isocyanate and hydroxyl groups; (2) A negative electrode slurry is coated and dried sequentially on each bottom coating layer to obtain a negative electrode sheet; wherein, the negative electrode slurry contains a negative electrode active material, a first conductive agent, a binder and a first solvent; the binder includes: styrene-butadiene rubber (SBR) and other binders, wherein the other binders include at least one of polyacrylic acid (PAA), lithium-ionized polyacrylic acid (PAA-Li), sodium carboxymethyl cellulose (CMC) and lithium carboxymethyl cellulose (CMC-Li).
[0008] In this invention, preferably, in step (2), the negative electrode slurry is coated and dried sequentially on one surface undercoating layer, and then the negative electrode slurry is coated and dried sequentially on another surface undercoating layer. Finally, the negative electrode sheet is obtained by rolling and slicing.
[0009] In this invention, preferably, the negative electrode slurry coated on each side is one or more layers; when the negative electrode slurry is coated in multiple layers, it is coated sequentially on the base coating layer, and the formulations of the multiple slurries can be the same or different; according to the above, when the negative electrode slurry coated on each side is multi-layered, only the first slurry layer is in contact with the base coating layer, and the other slurry layers are not in contact with the base coating layer.
[0010] In this invention, polyacrylic acid polymers containing at least one crosslinking functional group selected from nitrile, phenyl, epoxy, isocyanate, and hydroxyl groups can be synthesized according to conventional synthetic routes in the art; for example, the modified PAA used is prepared by a method comprising the following steps: General steps before PAA modification: (1) Add solvent to the reactor, start stirring, purge the air in the reactor with nitrogen three times, maintain a slight positive pressure with nitrogen, and stir at 150-250 r / min. (2) Add the main monomer AA acrylic acid to the reactor and stir until completely dissolved; then add the chain transfer agent (mercaptoethanol / isopropanol) and stir for 20 min. (3) Heat the system to the polymerization temperature: 70-80℃ for aqueous phase polymerization and 60-75℃ for organic solvent phase polymerization.
[0011] PAA Modification Steps
[0012] (1) Nitrile-modified PAA
[0013] ① After pretreatment, slowly add 15-20 parts by weight of acrylonitrile dropwise to the reactor over 1.5-2 hours. ② After the addition is complete, add ammonium persulfate (APS) aqueous solution in batches to initiate polymerization; maintain the reaction temperature at 70-80℃ for 5-6 hours, during which acrylic acid and acrylonitrile undergo free radical copolymerization, and -CN nitrile groups are grafted onto the side chains of the PAA molecule. ③ After the reaction is complete, cool to below 40℃; slightly remove trace amounts of unreacted acrylonitrile monomer under reduced pressure to obtain nitrile-modified PAA adhesive.
[0014] (2) Phenyl-modified PAA
[0015] ① Preparatory steps: Use isopropanol-deionized water mixed solvent (styrene has poor water solubility, so pure water alone cannot be used). ② Add 12-18 parts by weight of styrene to a small amount of isopropanol in a premixed solution and add it dropwise to the reactor over 1.5-2 hours. ③ After the addition is complete, add AIBN initiator and maintain the reaction temperature at 65-72℃ for 6-7 hours. The benzene ring of styrene will act as a side link and branch onto the PAA backbone. ④ Cool and remove isopropanol and residual styrene by vacuum distillation to obtain phenyl-modified PAA.
[0016] (3) Isocyanate-modified PAA
[0017] ① The reactor is pre-dried to remove water, and anhydrous isopropanol is used as the solvent, with nitrogen fully purging. Add acrylic acid (AA) and chain transfer agent, and stir to dissolve. ② Heat the system to 60-68℃, and slowly add 10-16 parts by weight of MOI monomer dropwise to the reactor over 1.5-2 hours. ③ Add AIBN initiator, and maintain the reaction temperature for 5-6 hours, grafting PAA side chains onto the -NCO isocyanate groups of MOI. ④ After the reaction is complete, cool; do not add water, and discharge directly to obtain an isocyanate-modified PAA organic solution.
[0018] (4) Epoxy-modified PAA
[0019] ① Preparatory work: Control the reaction temperature to ≤75℃, as excessively high temperatures will cause the epoxy groups to open and become ineffective. ② Add 14-20 parts by weight of glycidyl methacrylate dropwise at a uniform rate over 2 hours. ③ After the addition is complete, add the APS initiator and maintain the reaction temperature at 68-74℃ for 5-6 hours. Strictly prohibit excessively acidic pH and excessively high temperature to prevent the epoxy groups from hydrolyzing and opening. ④ Cool to room temperature and stop the reaction to obtain modified PAA with epoxy groups on the side chains. Do not distill under reduced pressure at high temperatures to avoid damaging the epoxy groups.
[0020] (5) Hydroxyl-modified PAA
[0021] ① Preparatory steps: Water can be used directly as a solvent. ② Add 12-22 parts by weight of hydroxyethyl acrylate (HEA) dropwise to the reactor at a uniform rate over 1.5-2 hours. ③ After the addition is complete, add the APS initiator and maintain the reaction temperature at 70-78℃ for 4-6 hours. The hydroxyl groups of the HEA side chains will be grafted onto the PAA polymer. ④ Cooling allows for slight decompression to remove residual monomers, yielding a hydroxyl-modified PAA aqueous solution with good water solubility, suitable for water-based primer slurries.
[0022] (6) Multifunctional modified PAA
[0023] ① Preparatory steps: At least two of the following monomers are selected: acrylonitrile, styrene, glycidyl methacrylate (GMA), MOI monomer, and hydroxyethyl acrylate (HEA). These monomers are then modified with the above methods to obtain multifunctional PAA.
[0024] According to the present invention, preferably, the drying thickness d1 of the base coating on each side is 0.1-5 μm, more preferably 0.2-2 μm.
[0025] According to the present invention, preferably, the crosslinking temperature of the primer adhesive is 60-140°C, more preferably 90-130°C; The preferred primer adhesive is nitrile-modified polyacrylic acid (nitrile-modified PAA).
[0026] According to the present invention, preferably, the primer slurry further includes: a second conductive agent and a second solvent; The dry mass ratio of the second conductive agent to the primer adhesive is (60-70):35, preferably (62-68):35.
[0027] According to the present invention, preferably, the coating speed of the negative electrode slurry is 2-120 m / min, more preferably 30-90 m / min.
[0028] According to the present invention, preferably, the drying temperature is 60-140°C.
[0029] According to the present invention, preferably, the drying thickness d2 of the negative electrode sheet is 100μm≤d2≤350μm, and more preferably 150μm≤d2≤250μm.
[0030] A second aspect of the present invention provides a negative electrode sheet prepared by the above-described preparation method.
[0031] According to the present invention, preferably, the peeling force of the negative electrode sheet is ≥8N / m.
[0032] A third aspect of the present invention provides a secondary battery comprising: a positive electrode, a separator, an electrolyte, and the aforementioned negative electrode.
[0033] In this invention, preferably, the cell of the secondary battery can be a pouch cell, a prismatic cell, or a cylindrical cell.
[0034] The technical solution of the present invention has the following beneficial effects: (1) The present invention improves the problem of adhesive floating by adding a base layer and utilizing the cross-linking reaction between the base adhesive and SBR.
[0035] (2) The negative electrode sheet of the present invention has improved adhesion, is compatible with existing production lines, has low industrialization cost, does not require modification of core equipment such as coating machine and oven, only requires adding a base coating process in the copper foil pretreatment stage, and the cross-linking reaction of base coating adhesive and SBR can be completed at traditional drying temperature, without additional heating or time extension cost, and is compatible with coating speed of 2-120m / min, which is in line with the existing high-speed production capacity rhythm.
[0036] (3) The peel strength of the prepared negative electrode sheet is ≥8N / m, which is ≥50% higher than that of the electrode sheet without bottom coating. The bottom coating adhesive is connected to the SBR through a chemical bond cross-linking structure. The bonding energy of the chemical bond is several times stronger than that of conventional electrostatic and riveting, which greatly enhances the bonding stability between the current collector and the active material layer and reduces the risk of electrode sheet falling off.
[0037] (4) The negative electrode sheet with a base coating and cross-linking has a capacity retention rate of ≥90% after 2000 cycles at 1C rate, which significantly improves the cycle life.
[0038] (5) The present invention has a wide range of applications and strong compatibility. The negative electrode slurry supports single-layer or multi-layer coating, and the electrode thickness can be adjusted from 100 to 350 μm (preferably 150 to 250 μm). It can also be used for various secondary cells such as soft pack, square shell, and cylindrical, and is adapted to the production needs of different types of lithium-ion batteries.
[0039] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0040] The above and other objects, features and advantages of the present invention will become more apparent from the more detailed description of exemplary embodiments of the invention in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the invention.
[0041] Figure 1 A front view schematic diagram of a negative electrode sheet according to an embodiment of the present invention is shown.
[0042] Figure 2 A schematic left-side view of a negative electrode sheet according to an embodiment of the present invention is shown.
[0043] Explanation of reference numerals in the attached figures: 1-Negative electrode sheet, 2-Copper foil, d1-Undercoating thickness, d2-Negative electrode sheet thickness. Detailed Implementation
[0044] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0045] The present invention is further illustrated by the following examples: In the following embodiments and comparative examples: The nitrile-modified PAA used was prepared by a method comprising the following steps: (1) Add deionized water to the reactor, start stirring, purge the air in the reactor with nitrogen three times, maintain a slight positive pressure with nitrogen, and stir at 200 r / min.
[0046] (2) Add 4 parts by mass of the main monomer acrylic acid AA into a reactor containing 6 parts by mass of deionized water and stir until completely dissolved; then add 0.05 parts by mass of chain transfer agent (isopropanol), stir at 300 r / min, and the aqueous phase polymerization temperature is 75℃. After reacting for 8 hours, take out the precipitate, add alkali solution to neutralize the pH to 6.5-9, and obtain an aqueous PAA solution.
[0047] (3) 20 parts by mass of acrylonitrile were slowly added dropwise to a reactor containing an aqueous PAA solution over a period of 1.8 h. After the addition was complete, 0.2 parts by mass of ammonium persulfate (APS) were added in batches to initiate polymerization. The reaction was maintained at 75°C for 6 h, during which acrylic acid and acrylonitrile underwent free radical copolymerization, and -CN nitrile groups were grafted onto the side chains of the PAA molecules. After the reaction was completed, the mixture was cooled to below 40°C. A small amount of unreacted acrylonitrile was slightly removed under reduced pressure to obtain a nitrile-modified PAA solution.
[0048] The specific test methods for the test items in the following embodiments and comparative examples are as follows: 1. Peel test method: (1) Cutting the electrode sheets After rolling, the negative electrode sheet is cut into 240mm lengths using a custom-made die. 20mm wide.
[0049] (2) Attaching and fixing the electrode plates
[0050] Take a flat, thin steel plate, approximately 200mm long and 50mm wide. First, apply a strip of double-sided tape (longer than the sample test length and the same width as the electrode) to the center of the steel plate, smoothing it firmly to ensure it adheres tightly to the center. Peel off the double-sided tape and attach the electrode to the tape. It is crucial to ensure a perfect fit between the electrode and the tape; otherwise, the width of the peel force test will change, reducing accuracy.
[0051] (3) Installation and testing
[0052] Turn on the tensile testing machine. It has two clamps, one above the other. Insert the steel plate with the pre-attached electrode into the lower clamp and secure it vertically. Insert the electrode without adhesive into the upper clamp and secure it, ensuring the electrode with adhesive tape is at a 180° angle to the one secured in the upper clamp. After securing the test sample, first calibrate and zero the machine. Set the test width, electrode peel length to 100mm, and peel speed to 50mm / min. Then start the test to obtain the peel strength curve and average value. When processing the data, delete the start and end segments of the test to obtain the standard curve. Based on the standard curve, the peel force of the electrode can be obtained.
[0053] 2. Cell internal resistance test method: (1) Place the cell to be tested on the test bench. (2) Turn on the battery internal resistance tester and select the 1kHz mode. (3) Clamp the terminal with a four-wire clamp and tighten it to fix the position of the clamp. (4) Perform a quick test and wait for the value to stabilize and stop changing. (5) Record the internal resistance (mΩ).
[0054] Example 1
[0055] (1) Preparation of the base coating slurry for copper foil 2: Acrylonitrile-modified PAA was used as the binder for the base coating. The acrylonitrile-modified PAA, conductive agent SP, and deionized water were mixed evenly to obtain the base coating slurry. The dry mass ratio of conductive agent SP to acrylonitrile-modified PAA was 65:35. The prepared base coating slurry was coated on the upper and lower surfaces of the 6μm copper foil and dried at 90℃. The thickness d1 of the single-sided base coating after drying was 0.5μm.
[0056] (2) Negative electrode slurry 1 and negative electrode slurry 2 were prepared. Both negative electrode slurry 1 and 2 contained graphite, conductive agent SP, SBR, CMC and water. The raw materials contained in negative electrode slurry 1 and 2 were mixed evenly to obtain the corresponding negative electrode slurry. Among them, the formula of negative electrode slurry 1 was graphite: conductive agent SP:SBR:CMC = 96:0.5:2.3:1.2 (mass ratio); the formula of negative electrode slurry 2 was graphite: conductive agent SP:SBR:CMC = 97.6:0.6:0.7:1.1 (mass ratio). Among them, the proportion of SBR in negative electrode slurry 1 was higher than that in negative electrode slurry 2. The single-sided coating surface density of negative electrode slurry 1 and 2 was 60 mg / cm³. 2 .
[0057] Negative electrode slurry 1 and negative electrode slurry 2 are sequentially coated onto one side of a dry base coating, and then dried. Negative electrode slurry 1 and negative electrode slurry 2 are then sequentially coated onto the other side of the dry base coating, dried, and rolled to obtain a negative electrode roll for later use. The roll is then sliced to obtain a negative electrode sheet. Negative electrode slurry 1 is in direct contact with the base coating, while negative electrode slurry 2 is not in contact with the base coating. The negative electrode coating speed is 70 m / min, and the drying oven sections have frequencies of 27, 25, 33, and 27 Hz, and temperatures of 90, 95, 105, and 95℃, respectively. Negative electrode sheet 1 (e.g., ...) Figure 1 and Figure 2 The total thickness d2 (as shown) is 240 μm.
[0058] (3) The positive electrode slurry comprises: lithium iron phosphate, conductive agent SP, PVDF and NMP. The raw materials for preparing the positive electrode slurry are mixed evenly to obtain the positive electrode slurry; wherein, in the positive electrode slurry, the ratio of lithium iron phosphate: conductive agent SP: PVDF is 97:1.5:1.5 (mass ratio); a layer of the above positive electrode slurry is coated on both sides of the aluminum foil, and the double-sided coating surface density is 520 mg / cm². 2 Then, the positive and negative electrode sheets are obtained by drying, rolling and die cutting. The air frequency of each section of the drying oven is 32, 32, 30 and 32 Hz, and the temperature is 105, 110, 100 and 105℃, respectively.
[0059] (4) After assembling the positive and negative electrode plates and the separator, electrolyte is injected, followed by formation and capacity testing to obtain the battery cell. The electrolyte, by total weight, includes: 82% solvent (EC+DMC+EMC+PC, EC:DMC:EMC = 3:4:3 (volume ratio), PC accounts for 3% of the total electrolyte mass), 13% lithium salt (LiPF6+LFSI, LiPF6 and LFSI mass ratio is 5:2), 0.5% additive VC, 3% additive FEC, and 1.5% additive DTD; the separator is: a separator with alumina ceramic coated on one side of a PP base film and PVDF adhesive coated on both sides, with a PP base film thickness of 9μm, an alumina ceramic thickness of 1μm, and a PVDF adhesive thickness of 1.5μm on each side.
[0060] The obtained battery cells were subjected to a series of electrical performance tests, and the test data are shown in Table 1.
[0061] Example 2
[0062] The negative electrode sheet was prepared according to the method of Example 1, with the only difference being that the thickness d1 of the single-sided bottom coating after drying was 5 μm.
[0063] Using the negative electrode sheet prepared in this embodiment, and the same positive electrode sheet, electrolyte, and separator as in Example 1, a battery cell was prepared according to the battery cell preparation method of Example 1; the obtained battery cell was subjected to a series of electrical performance tests, and the test data are shown in Table 1.
[0064] Example 3
[0065] The negative electrode sheet was prepared according to the method of Example 1, with the only difference being that the thickness d1 of the single-sided bottom coating after drying was 1 μm.
[0066] Using the negative electrode sheet prepared in this embodiment, the same positive electrode sheet and electrolyte as in Example 1, a battery cell was prepared according to the battery cell preparation method of Example 1; the obtained battery cell was subjected to a series of electrical performance tests, and the test data are shown in Table 1.
[0067] Example 4
[0068] The negative electrode sheet was prepared according to the method in Example 1, with the only difference being that the thickness d1 of the single-sided bottom coating after drying was 2 μm.
[0069] Using the negative electrode sheet prepared in this embodiment, and the same positive electrode sheet, electrolyte, and separator as in Example 1, a battery cell was prepared according to the battery cell preparation method of Example 1; the obtained battery cell was subjected to a series of electrical performance tests, and the test data are shown in Table 1.
[0070] Comparative Example 1
[0071] The negative electrode sheet was prepared according to the method of Example 1, except that the coating process was removed and the negative electrode slurry 1 and negative electrode slurry 2 were directly coated on the upper and lower surfaces of the copper foil according to the process method of Example 1 to prepare a negative electrode sheet with a total thickness of 240 μm.
[0072] Using the negative electrode sheet prepared in this comparative example, and the same positive electrode sheet, electrolyte, and separator as in Example 1, a battery cell was prepared according to the battery cell preparation method of Example 1; the obtained battery cell was subjected to a series of electrical performance tests, and the test data are shown in Table 1.
[0073] Table 1
[0074] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a negative electrode sheet, characterized in that, The preparation method includes: (1) A primer slurry is coated on the upper and lower surfaces of the copper foil to form a primer coating; wherein the slurry includes a primer adhesive, and the primer adhesive is a polyacrylic polymer containing at least one crosslinking functional group selected from nitrile, phenyl, epoxy, isocyanate and hydroxyl groups; (2) A negative electrode slurry is coated and dried sequentially on each base coating layer to obtain a negative electrode sheet; wherein, the negative electrode slurry contains a negative electrode active material, a first conductive agent, a binder and a first solvent; the binder includes: styrene-butadiene rubber and other binders, and the other binders include at least one of polyacrylic acid, lithium polyacrylic acid, sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
2. The preparation method according to claim 1, wherein, The dried thickness d1 of the base coating on each side is 0.1-5 μm, preferably 0.2-2 μm.
3. The preparation method according to claim 1, wherein, The crosslinking temperature of the primer adhesive is 60-140℃, preferably 90-130℃; The preferred primer adhesive is nitrile-modified polyacrylic acid.
4. The preparation method according to claim 1, wherein, The primer slurry further includes: a second conductive agent and a second solvent; The dry mass ratio of the second conductive agent to the primer adhesive is (60-70):35, preferably (62-68):
35.
5. The preparation method according to claim 1, wherein, The coating speed of the negative electrode slurry is 2-120 m / min, preferably 30-90 m / min.
6. The preparation method according to claim 1, wherein, The drying temperature is 60-140℃.
7. The preparation method according to claim 1, wherein, The drying thickness d2 of the negative electrode sheet is 100μm≤d2≤350μm, preferably 150μm≤d2≤250μm.
8. The negative electrode sheet prepared by the preparation method according to any one of claims 1-7.
9. The negative electrode sheet according to claim 8, wherein, The peeling force of the negative electrode sheet is ≥8N / m.
10. A secondary battery, characterized in that, The secondary battery comprises: a positive electrode, a separator, an electrolyte, and a negative electrode as described in claim 8 or 9.
